Reconstruction of Islamic Education Based on Social Capital: a Sociological Analysis of The Transformation of The Relationship Between Kyai and Santri in The Digital Era - Mohammad Muchlis Solichin; Muhammad Hasan; Ahmad Nadif Muhlisin; Tsaqif Fiqhan Muhammad (Ihsan Cahaya Pustaka, 2026)
The traditional relationship between kyai (Islamic scholars) and santri (students) in the pesantren institution has long been the cornerstone of Islamic educational culture in Indonesia. However, the rapid penetration of digital technology has disrupted the conventional boundaries of this relationship, prompting a re-examination of authority, trust, and reciprocity as core dimensions of social capital. Drawing on a qualitative sociological approach with data sourced from in-depth interviews, participant observation, and documentary analysis across selected pesantren in East Java, this article argues that the kyai–santri relationship is undergoing a dual process of erosion and reinvention. While digitalization has weakened traditional forms of hierarchical bonding social capital, it has simultaneously opened new avenues for bridging and linking social capital that expand the educational reach and relevance of the pesantren. The findings suggest that Islamic education can be meaningfully reconstructed by integrating digital literacy into pesantren pedagogy without abandoning the ethical and spiritual foundations of the kyai–santri relationship. Theoretical and practical implications for Islamic educational policy are discussed.